Free solvent isolation of Fe3O4 from magnetic material iron sand utilizing high-energy ball milling as adsorben remazol turquoise blue G-133 and remazol red RB-133 - Ramadhan, Muhammad; Fahmiati, Fahmiati; Alrum, Armid; La Ode Muhammad Zuhdi, Mulkiyan (Acta Chimica Asiana, 2023)
The extraction of Fe3O4 from iron sand frequently utilizes a highly concentrated HCl solution, which is hazardous to the environment. The high-energy ball milling method of separating Fe3O4 from iron sand might produce Fe3O4 without acids and maintains its magnetic characteristics with a yield of 81.87%. The FTIR results suggest that the Fe3O4 separation procedure with high-energy ball milling was effective in eliminating the silica pick after activation with 2 M NaOH, which was confirmed by SEM-EDS data indicating there was no silica on the material's surface. Fe3O4 was separated, allowing use as an adsorbent to treat textile industry waste such as Remazol Turquoise Blue G-133 and Remazol Red RB-133. The adsorption of Fe3O4 on these two dyes occurred at pH 5, and as adsorbate concentration, contact time, and adsorption temperature of Fe3O4 were raised, the adsorption capacity increased. Remazol Turquoise Blue G-133 and Remazol Red RB-133 have qmax values of 16.75 and 1.43 mg/g, respectively. The isothermal adsorption of Fe3O4 for the two dyes quite follows the Freundlich isothermal with KF values of 1.87 and 0.42 L/g and n values of 2.17 and 1.22, respectively, results suggest that the adsorption process occurs physically and forms a multilayer adsorption surface. These results are supported by data obtained from the adsorption kinetics, which shows that it follows the first-order adsorption kinetics. The dyes thermodynamics also showed positive results for ΔHo and ΔGo, indicating that the process of adsorption was endothermic and not spontaneous, but to the degree of disorder (ΔSo), Remazol Turquoise Blue G-133 outperformed Remazol Red RB-133.